If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-2 + -4x) = 70 (-2 * 5 + -4x * 5) = 70 (-10 + -20x) = 70 Solving -10 + -20x = 70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -20x = 70 + 10 Combine like terms: -10 + 10 = 0 0 + -20x = 70 + 10 -20x = 70 + 10 Combine like terms: 70 + 10 = 80 -20x = 80 Divide each side by '-20'. x = -4 Simplifying x = -4
| 0=t^3+t^2-10t+8 | | 7(6x-2)=-476 | | 5(-8+7x)=-40 | | -5(-2x+4)=90 | | -5(1x+7)=-20 | | 2(1+1x)=24 | | 19/20*32 | | -5(2+7x)=-10 | | 3.14*4*1= | | 32*19/20 | | 15a^2+7ab-2b^2=0 | | 3x-3=-38-2x | | 4(3+3c)=56 | | 6(x+1)(x+1)-14=0 | | 10(x-2)=-2+40 | | 10+4x=7x+4 | | -12=-2x+3 | | 8+x=-4x-32 | | (5/7)=(x/21) | | 4y=-2x-1 | | 0.009/9 | | x+4=76-5x | | 33-x=33 | | 0.09/18 | | 7x-3=3x+41 | | 11(-5+4)= | | -y-7=-12 | | 576+100=x | | 2+6x+6x=26 | | Log(2)523=x | | -6+3x+6x=93 | | (-13)(-13)= |